PEER ASSESSMENT RATING (PAR) INDEX CALCULATION ON 2D DENTAL MODEL IMAGE FOR OVER JET, OPEN BITE, AND TEETH SEGMENTATION ON OCCLUSION SURFACE - Muhammad Febrian Rachmadi; Ratna Rustamadji; Miesje Karmiati Purwanegara; sani Muhammad Isa; Benny Hardjono (Faculty of Computer Science - Universitas Indonesia, 2014)
Abstract Malocclusion is a clinical symptom, in which the teeth of maxilla and mandible are not located at the proper location. If malocclusion left untreated, it can lead to complications in the digestive system, headache, and periodontal disease disorders. Malocclusion problems involving abnormalities of teeth, bones, and muscles around the jaw are obligation of orthodontic specialists to treat them. The treatments can be varying based on the type of malocclusion, including tooth extraction and tooth braces. To know certain degree of malocclusion experienced by the patient, an assessment method called Peer Assessment Rating (PAR) Index is usually used by the specialist. To help the works of orthodontic specialists in Indonesia, a new automated calculation system based on 2D image of tooth model for PAR Index is being developed. In this paper, the calculation system for over-jet, open-bite, and teeth segmentation is developed. The result of the developed system is then compared with manual assessment done by orthodontic specialist, in order to verify the accuracy of the system.